Meditation and music intervention for improving pregnancy psychological health - Sharanoor Hussain; M Priya (Wolters Kluwer Medknow Publications, 2023)
Introduction: There is currently limited research investigating mindfulness-based interventions' effects on self-reported and physiological stress indicators among pregnant women in India. Thus, the study examined the effectiveness of music and meditation interventions on the psychological status of pregnant women in Lakhimpur, Assam. Materials and Methods: In this quasi-experimental study, 300 pregnant women in the first trimester were selected using purposive sampling. The samples were divided into experimental (60) and control (60). The experimental group was randomized into two subgroups: Meditation (30) and music intervention (30). Data were collected through a self-structured tool to assess pregnant women's psychological status. Analysis of variance and t-tests were used to analyze the data. Results: The study found that pregnant women working in the government sector had a significantly better psychological status (p = 0.050). While no significant difference was observed in the area of living with the psychological status of pregnant women. The meditation intervention showed gradual improvement during the third trimester (p < 0.001), while continuous listening to music significantly improved psychological status during the third trimester (p < 0.001). Conclusion: The study results could be utilized by health-care providers, policymakers, and stakeholders to implement interventions that enhance the mental health of pregnant women.